Distribuição espacial de HPA em sedimentos do estuário Piauí-Real - Santos, Ewerton (2015)
Polycyclic aromatic hydrocarbons are organic compounds present in the environment and considered potentially pollutants, in addition to have carcinogenic and mutagenic properties. These compounds are widespread in the different environment compartments, thus, the aim of this study is to validate a method for determination of 16 polycyclic aromatic hydrocarbons (PAH) prioritized by the United States Environmental Protection Agency (USEPA) in sediments. The samples were collected in the Piauí-Real estuarine system, located in the state of Sergipe. The validated method is based in the use of ultrasound extraction and gas chromatography with mass spectrometry detector analysis. We evaluated seven parameters for the validation: selectivity, linearity, detection and quantification limit, precision, accuracy and robustness. The results are considered satisfactory when compared to guidelines of specialized agencies, such as INMETRO, which enables the method application with reliability and safety requirements. In the samples analysis, the distribution of HPA is in the range of 4.9 and 301 ng g-1 of dry sediment. The use of diagnostic reasons made the evaluation of sources contamination possible, where most of the samples was considered uncontaminated and inputted from mixing sources.